Classical and Modern Review on Sneha Kalpana w.s.r to Ghrita Kalpana (International Journal of Ayurveda and Pharma Research, 2023)
Ayurvedic dosage forms hold a unique place in pharmaceutics and therapeutics. Sneha Kalpana is a group of products of medicated Taila and ghee. It is an Ayurvedic preparation of oleaginous medicine that is prepared with the use of Kalka (herbal paste of different parts of plants), Kwatha (specifically prepared decoction in accordance with Ayurvedic principles) or Drava Dravya (any other liquid such as milk, juices etc.) With suitable Sneha as base taken in specific proportion, both the ingredients are mixed and heated under a specific temperature to meet the desired therapeutic requirement. In the modern terminology, Sneha can be correlated with Lipids. Materials and Methods: Literature related to Sneha Kalpana and Lipids have been referred from various Ayurvedic texts, modern medical books, research papers and journals. Properties of Sneha Dravya, Sneha sources, phases of Sneha Kalpana, effect of Sneha Paka on therapeutics, Sneha dose, Anupana, shelf-life, lipids and their types have been explained and compiled from different sources. Conclusion: Sneha Kalpana is used to extract fat soluble active principles from drugs and also to increase permeability of drugs so that they can be absorbed easily through the cell membrane. It is the only dosage form that can be administered through all routes of body, viz., Nasya (nasal route), Tarpan (ocular route), Karnapooran (auditory route), Snehapan (oral route), Abhyanga (topical route), Basti (vaginal, urethral, anal route). In the Modern era, various dosage forms can be developed as novel drug delivery system (NDDS) utilizing the concept of Sneha Kalpana (Lipids) to increase the bio availability of drugs to show maximum therapeutic effect.